Quantifying Publication Rates and Time to Publication for American Urological Association Podium Presentations. Issue 3 (25th March 2022) - Chua, Kevin J.; Mikhail, Mark; Patel, Hiren V.; Tabakin, Alexandra L.; Doppalapudi, Sai Krishnaraya; Ghodoussipour, Saum B.; Kim, Isaac Y.; Jang, Thomas L.; Srivastava, Arnav; Singer, Eric A.
Abstract : Purpose: The American Urological Association (AUA) Annual Meeting serves as the premier platform for presenting unpublished research in urology. Among selected abstracts, podium presentations represent the most impactful submissions. While podium presentations receive a large audience through conference attendance and social media posts, it is unclear how often they manifest as publications in peer-reviewed journals. Materials and Methods: Podium presentations from the 2017 AUA Annual Meeting were reviewed. Abstracts were assessed for publication between January 1, 2015 and May 31, 2020 allowing for a 3-year window of publication and accounting for publications prior to the submission deadline. Abstract authors were individually searched with key terms being added sequentially until <30 results were generated in PubMed®. Abstracts were deemed published if at least 1 author and 1 conclusion matched a manuscript. Publication rate, time to publication, and 2019 journal impact factor were collected. Statistical analysis was performed by linear and logistic regression. Results: Of 872 podium presentations, 453 (51.9%) were published within 3 years. Median time from submission to publication was 12.5 months (IQR: 7.5–20.5). The number of articles published at 1, 2 and 3 years from submission was 203, 368 and 430, respectively. The median journal impact factor of publications was 3.2 (IQR: 2.0–5.8). Oncology studies (OR=1.21 [95% CI: 0.91–1.60], p=0.186) had similar rates of publication compared to non-oncology studies. Conclusions: While AUA podium presentations disseminate valuable data, approximately half were not published in peer-reviewed journals within 3 years. Therefore, care must be taken when promoting findings or adopting new practices based on these presentations alone.